Determination of Hexabromocyclododecane in Backcoated Textile Preparation - GHANEM, R.; BAKER, HUTAF; DELMANI, F.A. (Asian Journal of Chemistry, 2010)
A simple and reproducible chromatographic method for determination of one of the brominated flame retatardants (FRs), hexabromocyclododecane isomers is proposed, the mobile phase consisted of 80 % (v/v) acetonitrile aqueous solution. A simple quantitive extraction method using a soxhlet extraction is also proposed to extract hexabromocyclododecane from textile backcoated sample and a rapid chromatographic method, using spectrophotometric detection is described for the determination of hexabromocyclododecane. The proposed method is applied to determine the hexabromocyclododecane in a backcoated textile. A complete validation method for both extraction and analytical method is discussed. Linear calibration curve in range of 0.5-380 μg/mL is achieved. Detection limit are in the range 0.01 to 0.1 μg/mL.